2003
DOI: 10.2172/15010113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physical Properties of Transuranic Waste in Hanford Single-Shell Tanks

Abstract: range from 70 to 85 wt%; the reported water content is somewhat higher in Tank T-111 (85 to 90 wt%) and lower in a few samples from T-201 (~65 wt%). Most of the data for bulk solids samples, a matrix of waste solids and interstitial liquid, show bulk densities of 1.15 to 1.30 g/mL, and the density generally increases with decreasing water content. The shear strength estimates obtained from the extrusion methods were compared with the water content and bulk density of waste samples from the same core segments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Results with this methodology (termed "extrusion length") were generally within a factor of two or better of the ball rheometer measurements (typically accepted as being more representative of in situ waste conditions than laboratory measurements; for select saltcake DSTs. It was concluded that, in the absence of definitive in situ measurements, or in support of them, this extrusion length methodology is expected to produce representative results for the material's shear strength (Rassat et al 2003a). A relatively favorable comparison of shear vane and extrusion length results can also be made for AY-102 sediment (see data in , and the similarity of extrusion length and shear vane results in sludge is reported in Appendix F of Hu (2007). 3.8 Based on this extrusion length methodology, horizontal core extrusion videos from AZ-101 were investigated.…”
Section: Az-101 Sediment Shear Strengthmentioning
confidence: 94%
See 4 more Smart Citations
“…Results with this methodology (termed "extrusion length") were generally within a factor of two or better of the ball rheometer measurements (typically accepted as being more representative of in situ waste conditions than laboratory measurements; for select saltcake DSTs. It was concluded that, in the absence of definitive in situ measurements, or in support of them, this extrusion length methodology is expected to produce representative results for the material's shear strength (Rassat et al 2003a). A relatively favorable comparison of shear vane and extrusion length results can also be made for AY-102 sediment (see data in , and the similarity of extrusion length and shear vane results in sludge is reported in Appendix F of Hu (2007). 3.8 Based on this extrusion length methodology, horizontal core extrusion videos from AZ-101 were investigated.…”
Section: Az-101 Sediment Shear Strengthmentioning
confidence: 94%
“…developed the methodology to determine waste-extrusion behavior whereby the shear strength of a waste sediment is determined based on visually comparing the behavior of horizontal waste-core extrusion for simulants with known shear strength to that of Hanford Waste. An "extrusion length" methodology based on the simulant extrusion data of for estimating the yield stress in shear of Hanford Waste was developed in Rassat et al (2003a). This methodology relies on measuring the initial extrusion length of the waste core at plastic failure.…”
Section: Shear-strength Measurement Techniquesmentioning
confidence: 99%
See 3 more Smart Citations